A Prospective Study to Assess the Correlation of Neonatal Birth Weight with the Hemoglobin Level of the Mother During Pregnancy - Asma Iqbal, Mahwish Kanwal, Neeta Rani, Sadaf Abbas, Samina Lakhan, Nirmala Pawan (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The present study aims to the identification of an association between neonatal birth weights and the extent of anemia in mothers during pregnancy. Study design: A case-control study Place and Duration: This study was done in Sobhraj Maternity Hospital Karachi from November 2021 to November 2022 Methodology: A total of 1050 pregnant women were included in the study who later delivered babies in the given time frame. The blood samples of all the women were collected for the measurement of Hemoglobin (Hb) during the 16th to 19th week, then the 22nd to 24th week, and finally during the 34th to 36th week of pregnancy. The women were divided into four groups based on their hemoglobin levels. The patients in group 1 had Hb more than 10.1 gm/100ml and this group was considered as a control group. Group two constituted patients with mild anemia having Hb of 8.1 to 10 gm/100ml. Group 3 had patients with Hb 6.5-8 gm/100ml and were considered to have moderate anemia. The patients in the Group 4 had severe anemia with Hb of <6.5 gm/100ml. The weight of all the neonates was measured in the first 24 hours after delivery. A comparison of the birth weight of the neonates with the hemoglobin of mothers was done. Results: The prevalence of anemia was seen in210 (20%) womenwho had Hb lesser than 10 g/dl. Out of these, 33 (15.7%) presented with moderate anemia, and 177 (84.3%) had mild anemia. None of the patients had severe anemia. An overall drop in the Hb level was seen in the second trimester. The average birth weight of neonates born to women with Hb lesser than 10 g/dl was 2.7 kg, whereas, the average birth weight of babies of women with Hb more than 10 g/dl was 3.3 kg. The drop in Hb and the extent of anemia were highly related to the birth weight of neonates. Conclusion: There is a strong association between the severity of anemia and low birth weight (LBW). Maternal anemia is a potent factor behind intrauterine growth retardation (IUGR). Keywords:Birth weight, maternal hemoglobin, Anemia, Pregnancy